Glucosides from Mangrove Plant Avicennia Marina - Le, Viet Lan Huong; Tran, Thu Huong; Nguyen, Hoang Minh; Tran, Thu Ha; Pham, Thi Mai Huong; Tran, My Linh; Nguyen, Xuan Cuong; Nguyen, Hoai Nam; Chau, Van Minh; Nguyen, Van Thanh (Old Journal, 2019)
Avicennia marina (Forsk.) Vierh. (Verbenaceae) is a species of mangrove plant, distributed in the coastal mangrove forests of Northern and Southern Vietnam. Using combined chromatographic separations, three iridoid glucosides 2′-O-(4-methoxycinnamoyl)mussaenosidic acid (1), 2′-cinnamoyl-mussaenosidic acid (2), marinoid D (3), and a lignan glucoside syringaresinol-β-D-glucopyranoside (4) were isolated from the methanol extract of leaves of mangrove plant Avicennia marina. Structures of the isolated compounds were elucidated by spectroscopic methods including one dimensional (1D)- and (2D)- NMR, electrospray ionization mass spectrometry (ESI-MS), and also by comparison with the literature data. Compound 4 is reported for the first time from this plant.